1997
DOI: 10.1002/j.1556-6978.1997.tb00538.x
|View full text |Cite
|
Sign up to set email alerts
|

An Interactional Model for Empowering Women in Supervision

Abstract: Gender-related power differences have been observed in supervision. Empowering women involves attending to women's need for connection in interactions. An interactional model for encouraging connected power in supervision is presented.One goal of successful supervision is to facilitate the development of the trainee so that he or she can achieve a degree of professional autonomy (Hogan, 1964 1995) pointed out the difficulty for supervisors of attending to the technical and ethical demands of the profession w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Furthermore, socially and culturally defined gender roles and expectations are brought into supervision (Ancis & Ladany, 2010;Brodsky, 1980;Holloway & Wolleat, 1994;Inman & Ladany, in press;Munson, 1997;Stevens-Smith, 1995). Several authors have described theoretical models (Munson, 1997;Nelson, 1997) or have made recommendations regarding gender issues in supervision (Ancis & Ladany, 2010;Bernstein, 1993;Brodsky, 1980;Nadelson, Belitsky, Seeman, & Ablow, 1994;Stevens-Smith, 1995;Twohey & Volker, 1993); however, only a few have examined gender issues empirically (Baker, 1991;Budd, 1994;Claridge, 1994;Gullotta-Gsell, 1984;Horwitz, 1990;Johnson, 1997;Nelson & Holloway, 1990;Robyak, Goodyear, & Prange, 1987;Schiavone & Jessell, 1988;Schwartz, 1994;Walker, Ladany, & Pate-Carolan, 2007;Worthington & Stern, 1985). These studies are extremely varied in design and focus, and perhaps as a result, their findings are inconsistent and inconclusive (Holloway & Wolleat, 1994;Munson, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, socially and culturally defined gender roles and expectations are brought into supervision (Ancis & Ladany, 2010;Brodsky, 1980;Holloway & Wolleat, 1994;Inman & Ladany, in press;Munson, 1997;Stevens-Smith, 1995). Several authors have described theoretical models (Munson, 1997;Nelson, 1997) or have made recommendations regarding gender issues in supervision (Ancis & Ladany, 2010;Bernstein, 1993;Brodsky, 1980;Nadelson, Belitsky, Seeman, & Ablow, 1994;Stevens-Smith, 1995;Twohey & Volker, 1993); however, only a few have examined gender issues empirically (Baker, 1991;Budd, 1994;Claridge, 1994;Gullotta-Gsell, 1984;Horwitz, 1990;Johnson, 1997;Nelson & Holloway, 1990;Robyak, Goodyear, & Prange, 1987;Schiavone & Jessell, 1988;Schwartz, 1994;Walker, Ladany, & Pate-Carolan, 2007;Worthington & Stern, 1985). These studies are extremely varied in design and focus, and perhaps as a result, their findings are inconsistent and inconclusive (Holloway & Wolleat, 1994;Munson, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…A number of writers have suggested that supervisors incorporate gender issues when assisting trainees with conceptualizations (Ault-Riche, 1988;Bernstein, 1993;Ellis & Robbins, 1993;Holloway & Wolleat, 1994;Munson, 1987;Nelson, 1997;Stevens-Smith, 1995;Taylor, 1994;Twohey & Volker, 1993). In addition, there are a number of empirically based studies that examine gender dynamics within the context of supervision (Gatmon et al, 2001;Granello et al, 1997;Martinez et al, 1999;Nelson & Holloway, 1990;Sells et al, 1997).…”
mentioning
confidence: 99%
“…Supervisory style emphasizes the importance of procedures such as regular conferences with staff, review of case records and time studies, and supervisory procedures supporting worker autonomy, responsibility, selfinitiation, and independent decision-making. Hipp and Munson (1995) and Nelson (1997) encourage a partnership model, as opposed to the traditional hierarchical models, that promote collaborative learning and the pursuit of client and worker goals. However, neither of these studies investigated the relationship between supervision and worker self-efficacy attitudes toward their child welfare tasks.…”
Section: Frontline Supervisionmentioning
confidence: 97%